Semi-squat exercises with varying levels of arterial occlusion pressure during blood flow restriction training induce a post-activation performance enhancement and improve vertical height jump in female football players - Sun, D.; Yang, T. (Journal of Sports Science & Medicine, 2023)
Low-load blood flow restriction training (BFRT) has been shown to induce a significant increase in muscle activation. However, low-load BFRT to augment the post-activation performance enhancement (PAPE) has not been previously examined. This study aimed to examine the PAPE of low-intensity semi-squat exercises with varying pressure BFRT on vertical height jump performance. Twelve elite athletes from the Shaanxi Province women`s football team volunteered to participate in this study for 4 weeks. Participants completed four testing sessions that included one of the following at random: (1) non-BFRT, (2) 50% arterial occlusion pressure (AOP), (3) 60% AOP, or (4) 70% AOP. Muscle activity of the lower thigh muscles was recorded using electromyography (EMG). Jump height, peak power output (PPO), vertical ground reaction forces (vGRF), and rate of force development (RFD) were recorded for four trials. Two-factor repeated measures analysis of variance (ANOVA) showed that semi-squat with varying pressure BFRT had a significant impact on the measured muscle EMG amplitude and MF value of vastus medialis, vastus lateralis, rectus femoris, and biceps femoris (P < 0.05), and MF value decreased with increasing pressure. Muscle activation (EMG amplitude) did not change further. The EMG amplitude of the gluteus maximus was significantly decreased by semi-squat training with different pressures (P < 0.05), while that of the gluteus maximus muscle was gradually increased by non-BFR with semi-squat training (P > 0.05). The 50% and 60% AOP BFRTs significantly increased jump height, peak power, and force increase rate (RFD) after 5 min and 10 min of rest (P < 0.05). This study further confirmed that low-intensity BFRT can significantly increase lower limb muscle activation, induce PAPE, and improve vertical height jump in female footballers. In addition, 50% AOP continuous BFRT is recommended for warm-up activities.